Dissenting Opinion Hakim Pada Putusan Mahkamah Agung dalam Perkara Merek Terkenal Yumi Katsura dan Prada - Afiyah Qurrota Ayun; Asep Syarifuddin Hidayat; Fitriyani Zein (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2019)
Abstract:The problem examined in this study is related to the Dissenting Opinion of Judges in the Supreme Court's Decision in the Famous Brand Case of Yumi Katsura and PRADA. Problems related to the judges' consideration that stated dissenting opinions in famous trademark cases at the cassation level were seen from the Trademark Law, the Law on Judicial Power and the implications of the dissenting opinion on the famous brand case of Yumi Katsura and PRADA. This study uses qualitative research that is the type of data and analysis that is used is narrative, in the form of statements that use reasoning. The results of the study showed that the judges' consideration that stated dissenting opinion was more correct and correct, in the decision No. 310 K/Pdt. Sus-HKI/2013 based on the Law on Trademarks and facts at the hearing, while in the decision Number 164 K/Pdt . SUS-HKI/2016 besides based on the Trademark Law, also based on the Supreme Court Jurisprudence Number 2279/PK/Pdt/1992 and Number 1596 K/Pdt/1983. Then the implication of the judge's dissenting opinion on the case of a famous brand can provide knowledge about the interpretation of the phrase equality in essence and the interpretation of the criteria of a well-known brand as well as to the verdict handed down while still taking the most votes.Keywords: Dissenting Opinion, Famous Brand, Yumi Katsura and PRADA